Networked Academic Societies in Collaborative Development of e-Learning Courses - Stamatis, Demosthenes; Kefalas, Petros; Tsadiras, Athanasios (Proceedings of the International Conference on Networked Learning, 2006)
In this paper, we describe a framework for supporting Networked Academic Societies towards the collaborative development of e-Learning courses. Academics with common interests in teaching could combine their knowledge into the development of integrated e-Learning courses. This is a hard task, since the communication overhead is rather big to be ignored by busy academics, unless there are specifically designed ICT-based tools which could facilitate the collaboration. Groupware systems could fit this purpose to some extend, but they are rather general and need to be extended by specialised software modules. For this reason we suggest TeachWare as the necessary ICT collaboration system needed to support Networked Academic Societies, for which we provide specifications and give its abstract architecture.